Millennial Capitalism and the Culture of Neoliberalism - Allan, Sekula; Caitrin, Lynch; Comaroff, Jean; Comaroff, John L.; David, Harvey; Elizabeth, Povinelli; Fernando, Coronil; Francis, Nyamnjoh; Hylton, White; Irene, Stengs; Jean, Comaroff; Jeffrey, Zimmermann; et al. (a Public Culture Book, 2001)
The essays in Millennial Capitalism and the Culture of Neoliberalism pose a series of related questions: How are we to understand capitalism at the millennium? Is it a singular or polythetic creature? What are we to make of the culture of neoliberalism that appears to accompany it, taking on simultaneously local and translocal forms? To what extent does it make sense to describe the present juncture in world history as an "age of revolution," one not unlike 1789-1848 in its transformative potential?In exploring the material and cultural dimensions of the Age of Millennial Capitalism, the contributors interrogate the so-called crisis of the nation-state, how the triumph of the free market obscures rising tides of violence and cultures of exclusion, and the growth of new forms of identity politics.